Evaluation Of The Hospital Billing System's Implementation In Recording Outpatient And Inpatient Payments Using The Pieces Method - Widya Yanti Sitohang; Ronel Polin Sihombing; Ermi Girsang (Universitas Pahlawan Tuanku Tambusai, 2025)
Electronic billing simplifies and speeds up patient billing. This study will evaluate the system's performance, information, economics, control/security, efficiency, and service (PIECES) using the analytical model. This study examines RSU Royal Prima Medan's PIECES hospital billing system's outpatient and inpatient payment recording. A mixed-methodologies study uses quantitative and qualitative methods. This study sampled 200 patients quantitatively and seven informants qualitatively. Quantitative data analysis employed univariate analysis, while qualitative used triangulation. This study found that RSU Royal Prima Medan's hospital billing system for outpatient and inpatient payments performed well in performance, information, economics, control, efficiency, and service. The challenges include rare network problems. This study found that RSU Royal Prima Medan's PIECES hospital billing system for outpatient and inpatient payments is working well. RSU Royal Prima Medan should develop the system to properly use it in the future by training officers, evaluating them, and supervising them to reduce errors and maximize patient care.